Charakterystyka gruntów spoistych o bardzo wysokiej granicy płynności z terenu Środkowego Nadodrza = Characteristic of cohesive grounos of very high liquid limit from Środkowe Nadodrze area - Gontaszewska-Piekarz, Agnieszka; Kraiński, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Paper presents description of cohesive grounds of very high liquid limit. Such grounds are about 20% of all clayey grounds from Środkowe Nadodrze area. Authors show geological history and sedimentation environmcnt of investigated grounds. A basie geotechnical parameters was also described and opportunities of using some nomogram was shown.
Keywords: grunty spoiste; iły; plastyczność; granica płynności; cohesive grounds; clays; liquid limit